HUBUNGAN ANTARA FAKTOR KETURUNAN, AKTIVITAS MELIHAT DEKAT DAN SIKAP PENCEGAHAN MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS RIAU TERHADAP KEJADIAN MIOPIA - Sepnita Usman; Efhandi Nukman; Eka Bebasari (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Myopia is a refractive error with incidents between 50% to 80,3% at some hospitals in Indonesia. Based on World Health Organization, the prevalence of myopia is increasing. The prevalence of myopia among medical students is nearly twice as high as in general population. Risk factor that associated with myopia is genetic or herediter, near work activitis and prevention attitudes. The aim of this study is to determine the relationship between heredity, near work activities and prevention attitudes in students of Faculty Medicine of Riau University with incidence of myopia. This study was analytic observational cross sectional study. The subjects in this study are medical students of Faculty Medicine of Riau University grade 2010, 2011 and 2012. Total samples in this study is 85 people taken with stratified random sampling technique. The data of relationship between heredity with myopia was analyzed by chi-square test, relationship between myopia with near work activities for variable reading book and work study task was analyzed by kolmogorov-smirnov test, for variable reading for pleasure (hobby), watching televison, using computer or laptop was analyzed by chi-square test and relationship between prevention attitudes with myopia was analyzed by kolmogorov-smirnov test. The result of this study showed a significant association for heredity with myopia (p = 0,001). There were no statistically association between reading and work study task (p = 0,492), reading for pleasure or hobby (p = 0,895), wathcing television (p = 0,774), using computer or laptop (p = 0,680). No association between prevention attitudes with myopia (p = 0,144).Keyword : myopia, heredity, near work activities, prevention attitudes